TRAINING AND ACTIVITIES FOR CULTURAL AND EDUCATIONAL INSTITUTIONS IN THE 20-30S OF THE 20TH CENTURY - Asfandiyorovich, Narmanov Feruz (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the training and activities of workers in cultural and educational institutions that served as the main object in the promotion and promotion of the Soviet system from the 20-30s of the 20th century, the contradictions in staff training and the promotion of these institutions. The impact on social life has been studied.